Editorial: Peruvian university life - El Director (2008)
Since Peruvian university life has been more focused on teaching than on research, it is difficult but at the same time indispensable to work for a change in the academic culture that favors a greater dedication of professors to research and publication. With this in mind, the IECOS management has taken the initiative to call for a competition to select the best research projects and has simultaneously extended an open invitation to all teachers to publish in this journal. Since it is necessary to create favorable conditions for the research and writing work itself, we have provided those who have requested it with technological means and space in the IECOS office itself. In addition, we are offering economic incentives for the work of professors and students who win a contest.